Placental microRNA Expression Is Not Altered by Maternal Obesity and Fetal Overgrowth - Neda Ghaffari; Samuel Parry; Michal A. Elovitz; Celeste P. Durnwald (Thieme Medical Publishers, Inc., 2016)
Abstract Objective The epigenetic mechanisms underlying fetal metabolic programming are poorly understood. We studied whether obesity is associated with alterations in placental miRNA expression. Study Design A cross-sectional study was performed, including (1) normal-weight women (BMI 20-24.9 kg/m2) and normal-birth-weight (BW) infants (2,700-3,500 g) (n = 20), (2) normal-weight and macrosomic infants (BW ≥ 4,000 g) (n = 10), (3) obese (BMI ≥ 35 kg/m2) and normal BW infants (n = 16), and (4) obese and macrosomic infants (n = 10). All had term deliveries (37-41 weeks) and normal glucose tolerance (1 hour GCT < 7.2 mmol/L [130 mg/dL]). The expression of 5,639 placental miRNAs was assessed using miRNA microarray. Differential miRNA expression was determined using two-way ANOVA and pairwise contrasts, with the Benjamini-Hochberg (BH) correction. MiRNAs with Z-scores ≥ 2 and false discovery rate (FDR) < 20% were considered significant. Results Principal components analysis demonstrated similar global miRNA expression profiles among groups. Of 5,639 miRNAs, only 5 were significantly different between obese and controls, which were not validated by quantitative polymerase reaction. Conclusion There was no difference in placental miRNA expression associated with obesity or overgrowth. Aberrant placental miRNA expression is an unlikely mechanism underlying fetal metabolic programming related to maternal obesity.